Taliglucerase alfa in the longterm treatment of children and adolescents with type 1 Gaucher disease: the Albanian experience - Paskal Cullufi; Sonila Tomori; Virtut Velmishi; Agim Gjikopulli; Ilir Akshija; Aferdita Tako; Ermira Dervishi; Gladiola Hoxha; Marjeta Tanka; Erjon Troja; Mirela Tabaku (Frontiers in Pediatrics, 2024)
IntroductionEnzyme replacement therapy is already recognized as the gold standard of care for patients with Gaucher disease. Taliglucerase alfa is one of the three alternatives recommended for treatment of Gaucher disease in children and adults.AimThis study aims to evaluate the long-term efficacy and safety of Taliglucerase alfa in children and adolescents with Type 1 Gaucher disease.Patients and methodsOver a six-year period, we monitored the efficacy of continuous treatment in 10 patients by assessing various parameters, including hemoglobin concentration, platelet count, liver and spleen volume, bone mineral density, glucosylsphingosine level, chitotriosidase activity, and growth parameters. Safety was evaluated by immunogenicity and adverse event monitoring.ResultsThe mean age of patients was 13.4 ± 3.6 years and the treatment duration was 60.24 ± 13.4 months. From baseline to end line the parameters change as follows: hemoglobin concentration improved from 12.7 (±1.3) to 14.6 (±1.5) and platelet count from 180 (±74) to 198 (±79). The spleen volume, was reduced by 46% (p = 0,007). The chitotriosidase activity decreased from 4,019.7 (±3,542.0) nmoles/ml/hr to 2,039.5 (±1,372.2) nmoles/ml/hr (46% reduction). Glucoylsphingosine level dropped from 119.2 (±70.4) ng/ml to 86.2 (±38.1) ng/ml, indicating a reduction of 28%. Bone mineral density Z-score, improved from −1.47 (±1.76) to −0.46 (±0.99) (69.7% reduction). Out of the 1,301 total administrations, our patients reported only 37 (2.8%) infusion-related adverse events which were mild and transitory.ConclusionTaliglucerase alfa exhibits good efficacy and a safe profile in the treatment of children and adolescents with Type 1 Gaucher disease.